Pattern of use of a small bay in northern Brazil by Sotalia guianensis (Cetacea: Delphinidae) - Torres, D.; Beasley, C. R. (Amazoniana, 2003)
The abundance, movements and behaviour of Sotalia guianensis were studied between 1999 and 2001 in the Emborai Bay on the northeastern coast of Para, Brazil. Dolphins are not distributed regularly around the bay and the population size is estimated to be approximately 150 individuals. Dolphins enter the bay to feed, especially at low tide.
Keywords: Golfinhos